Case Report: A playful digital-analogical rehabilitative intervention to enhance working memory capacity and executive functions in a pre-school child with autism - Panesi, Sabrina; Dotti, Marina; Ferlino, Lucia (Frontiers in Psychiatry, 2023)
Background Autism Spectrum Disorder (ASD) is often associated with deficits in Working Memory Capacity (WMC) and Executive Functions (EFs), as early as the first years of life. Research has shown that, even young children with ASD, WMC and EF deficits can be effectively addressed through interventions employing digital and/or analogical tools. Early intervention is important because executive dysfunction can negatively impact on the quality of life, both of children and their families. However, very few studies have been carried out involving intervention with pre-schoolers with ASD. To fill this gap, we developed an intervention that promotes pre-schoolers’ WMC and EFs by employing both digital apps and analogical playful activities. This study reports on the feasibility of this intervention, which was carried out in a rehabilitative context. Methods A male pre-schooler diagnosed with ASD was engaged in a total of 17 intervention sessions, all held in a clinical context, over a nine-week period. Outcomes were measured using a battery of pre- and post-treatment tasks focusing on WMC, EFs and receptive language. The clinician who administered the intervention made written observations and noted any improvements in the child’s performance emerging from the digital and analogical activities. Results The pre- and post-test scores for the cognitive tasks revealed qualitative improvements in the following cognitive domains: (a) WMC in the language receptive domain; (b) updating in WMC; (c) inhibition, specifically concerning control of motor response; (d) receptive vocabulary. Furthermore, when monitoring the child’s performance, the clinician noted improvement in almost all the playful activities. Particularly notable improvements were observed in interaction with the apps, which the child appeared to find very motivating. Conclusion This study supports feasibility of a playful digital-analogical intervention conducted by a clinician in a rehabilitation context to promote cognitive abilities in pre-schoolers with ASD. Further studies are needed to establish whether the intervention’s effectiveness can be generalized to a broad sample of children with ASD.